Alexithymia and attachment dimensions in relation to parental burnout: A structural equation modelling approach - Dawid Konrad Ścigała; Joanna Sikora-Ścigała; Elżbieta Zdankiewicz-Ścigała (PLoS ONE, 2025)
Background Parental burnout is a chronic, parenting-specific syndrome marked by emotional exhaustion, emotional distancing from one’s children, and reduced parental fulfilment. Although links of insecure attachment and emotion-processing difficulties with parental burnout have been reported, their joint associations remain underexplored. This study applied Structural Equation Modelling (SEM) to examine whether alexithymia—defined as difficulties identifying and describing feelings and externally oriented thinking, assessed with the Toronto Alexithymia Scale (TAS-20)—is involved in the associations between attachment orientations and parental burnout, and whether these associations differ by sex. Methods A cross-sectional sample of 440 Polish parents (229 women, 211 men; 52.1% women; M = 38.91, SD = 7.33; age range = 21−61) completed the Experiences in Close Relationships—Relationship Structures Questionnaire (ECR-RS), the Toronto Alexithymia Scale (TAS-20), and the Parental Burnout Assessment (PBA). Sex-stratified SEMs were estimated. Results In women, higher avoidance toward the mother was directly associated with higher burnout, whereas anxiety toward the mother related to burnout indirectly via elevated alexithymia. In men, avoidance of the mother was directly associated with burnout, while anxiety toward the mother related to burnout indirectly through alexithymia. Parallel patterns emerged for paternal attachment in sex-specific models. Conclusions Across sex-stratified models, alexithymia was consistently implicated in the associations between insecure attachment and parental burnout. The patterns differed for women and men, underscoring the value of emotion-focused and attachment-informed support tailored by sex. Findings reflect cross-sectional associations and do not imply causality.